ENT 530 Business Plan : Lavandula Sdn Bhd / Siti Sarah Alyasa Gan ... [et al.] - Alyasa Gan, Siti Sarah; Rizal, Nurul Shazreen; Azahari, Nur Affrina; Nordin, Muhammad Afiq Faiz; Ramli, Muhammad Idham (2018)
kin care is a practice that protects skin integrity, enhances its beauty and relieves skin conditions if the skin experiences any irritation. Due to this, our company has innovated facial cleansers that are not just convenience, but also problem-solving. Our company's name is Lavandula. This company offers very interesting facial cleansers as we mainly use natural ingredients and they are made with papers. We develop two types of facial cleansers which are called the Coconut Facial Cleanser and Aloe Vera Facial Cleanser. We believe that the society needs this product as it is very convenient especially for travellers. Our product is not just offering nonnal liquid nor bar soaps facial washes, but they are made in the form of paper that is soluble towards water. With the touch of water, these facial cleansers will turn into normal facial cleansers. We hope that our product will help aid our customers to find their right daily facial cleanser. As travelers, mainly backpackers experience the problem in limitation of 100 millimeter for liquid substances, this product is very much suitable for them as it is not in the form of liquid but paper. To provide better quality of our product, we will be dealing with National Pharmaceutical Regulatory Agencies (NPRA) to get Good Manufacturing Practices (GMP) certificate. With this, consumers will be more confident to buy and use our product.